-8(p+2)+p=4(p+3)

Simple and best practice solution for -8(p+2)+p=4(p+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8(p+2)+p=4(p+3) equation:



-8(p+2)+p=4(p+3)
We move all terms to the left:
-8(p+2)+p-(4(p+3))=0
We add all the numbers together, and all the variables
p-8(p+2)-(4(p+3))=0
We multiply parentheses
p-8p-(4(p+3))-16=0
We calculate terms in parentheses: -(4(p+3)), so:
4(p+3)
We multiply parentheses
4p+12
Back to the equation:
-(4p+12)
We add all the numbers together, and all the variables
-7p-(4p+12)-16=0
We get rid of parentheses
-7p-4p-12-16=0
We add all the numbers together, and all the variables
-11p-28=0
We move all terms containing p to the left, all other terms to the right
-11p=28
p=28/-11
p=-2+6/11

See similar equations:

| 2(x+3)=x=9 | | -6(n-3)=5(4=n) | | X2+6x+5=45 | | 4+4x+9=2x^2 | | F=2.25+0.25(m-1) | | y2/3-10(y1/2)+16=0 | | |3x|=|2x+10| | | √x+1-√2x-5=√x-2 | | y2/3-10(1/2)+16=0 | | 500-20*n=220 | | 9=6/2x | | 1=6/2x | | 548+29.50*n=2023 | | 1/2x+2=2x-7 | | (x^2-x+1)^3=0 | | (2/3x)=8/9 | | 45*n+60=285 | | 36=1.2g | | 420a-1337(a(a2(a)(a)))=69 | | 3(x-5)=5x-29 | | -4+9(6x-10)=(50x-9) | | 3/4x+1/4=6/4 | | -4+9(6x-10)=(5x-1) | | -4+9(6x-10)=(54x-13) | | -7u+5(u+7)=37 | | -4+9(6x-10)=(54x+13) | | -4+9(6x-10)=(54x+5) | | 1.25*n+6.75=31.75 | | 7w-20=2(w-8) | | (3x4x1)+4=16 | | 2x6x3)+4=40 | | 9(2m=6)=2-8m |

Equations solver categories